Colloidal silica as a grouting material for the temporary encapsulation of heat-generating radioactive waste during removal and transport operations: A proof of concept - Pagano, Arianna Gea; El Mountassir, Gráinne; Lunn, Rebecca Jane (Frontiers in Energy Research, 2023)
Hazardous nuclear waste is produced at all stages during the nuclear fuel cycle. The removal operations of nuclear waste from nuclear reactors and/or storage facilities, such as spent fuel pools and storage silos, pose a hazard for the workforce and the environment, due to the potential release of radioactive particulates and loss of radioactive debris. The development of innovative techniques to address this issue is desirable. A potential technology to inhibit particulate release during nuclear waste removal and transport operations is colloidal silica grouting. Colloidal silica is an aqueous suspension of silica (SiO2) nanoparticles, able to provide immobilisation of particulates within a hydrogel matrix. In this study, an experimental investigation was carried out to simulate colloidal silica grouting operations around objects at temperatures of 60 and 120 °C, to simulate radioactive waste in standard storage conditions, and during loss of cooling/loss of coolant accident scenarios. The results of the experimental campaign confirm the suitability of colloidal silica to safely remove and transport heat-generating radioactive waste. Critical parameters for designing the silica grout mix, in order to optimise the performance of the hydrogel upon exposure to temperature in different scenarios, are identified and discussed.